Words Take The World : Ekploitasi AS Terhadap Indonesia Sebagai Negara Periphery Pada Era Digital 2014 - Pradipta, Christian Aditya (Global and Policy Journal of International Relations, 2015)
ABSTRACTUnited States is often defined as Big Power and able to control the world through its power. In digital era within Communication International explain how U.S control periphery states is symbolized by Indonesia and get its economy interest. In digital era which is defined as era to free access of information giving high benefit for U.S to exploit Indonesia. As internet as important tool, U.S using internet to get economy access to Indonesia. With some indicators as internet penetration, internet consumptions, time spend on internet, e-commerce level and media online expenditure, become the basis asumptions of this research. The data explained how U.S exploit Indonesia through its online media.Keywords : U.S., Digital Era, Indonesia, Internet, Economy Interest.DOI:https://doi.org/10.33005/jgp.v3i02.1940